Transcriptome profiling to identify key mediators of granulosa cell proliferation upon FSH stimulation in the goose (Anser cygnoides). Issue 4 (4th July 2018) - Du, L.; Gu, T.; Zhang, Y.; Huang, Zhengyang; Wu, N.; Zhao, W.; Chang, G.; Xu, Q.; Chen, G.
ABSTRACT: 1. The low reproductive performance of geese has seriously hampered the development of the industry. Reproductive performance, particularly the egg laying rate mainly depends on the development of the follicle. Previous studies have shown that follicle-stimulating hormone (FSH) plays an important role in the process of follicular development, but the exact underlying mechanism remains unclear. 2. This study showed that FSH stimulated granulosa cell proliferation in a dose-dependent manner. The effect of FSH treatment on granulosa cell proliferation was greatest at a dose of 100 mIU/ml FSH for 24 h. 3. Secondly, the effect of different concentrations of FSH on goose granulosa cell proliferation was investigated, and de novo transcriptome assembly and gene expression analysis performed using short-read sequencing technology (Illumina). High-throughput sequencing results yielded 62.61 M reads and 7.8 G base pairs from granulosa cells treated with 100 mIU/ml FSH. These reads were assembled into 65, 757 unigenes (mean length: 705 bp) with an N50 of 903 bp. A total of 110 upregulated and 510 downregulated differentially expressed genes (DEGs) were identified by RNA-seq. 4. Functional analysis by gene ontology (GO) and KEGG pathway annotation indicated that hormone biosynthesis (GO:0042446), positive regulation of hormone secretion (GO:0046887), steroid biosynthesis, oxidative phosphorylation and carbon metabolism pathways were involved in FSH-mediated proliferation of goose granulosa cells. 5. After screening, a group of key responsive genes including superoxide dismutase 1, fatty acyl-CoA reductase 1, transforming growth factor-beta receptor-associated protein 1 and follistatin were tested by real-time reverse transcription PCR to confirm differential expression in granulosa cells stimulated by FSH. 6. FSH-stimulated goose granulosa cells and DEG profiling data provided comprehensive gene expression information at the transcriptional level that could promote better understanding of the molecular mechanisms underlying follicle development in response to FSH stimulation.